The Schemes Funding Analyisis for Technology Commercialization: A Case Study - Sutopo, Wahyudi; Astuti, Rina Wiji; Yuniaristanto, Yuniaristanto (Metris: Jurnal Sains dan Teknologi, 2017)
Funding is an important aspect in doing commercialization of the results of research based technology. Adequate funding is needed to develop successful research. This article is focused on developing a funding strategy for technology commercialization, on the condition where the funds owned by the researcher is not sufficient, the efforts need to do is find the source of funding from the other funding source. This research methodology was conducted by identifying an alternative access to the finance commercialization of technologies that possible and analyzing detail on each scheme by collecting primary data through interviews and support with some secondary data. The data were collected from interviews with the Technology Transfer Office (TTO) of universities in Indonesia; questionnaires and published material from some universities and research centers and Ministry of Science, Technology, and Higher Education of Indonesia. We also made a case study of a comparative analysis between Indonesia and Malaysia. The collected data were transcribed and analyzed with mapping analysis based on the criteria for each funding scheme. Conclusions are drawn from the study findings and recommendation made.